1995
DOI: 10.1161/01.str.26.11.2067
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Transcranial Doppler High-Intensity Transient Signals in Patients With Potential Cardiac Sources of Embolism

Abstract: HITS are common phenomena in patients with potential cardiac sources of embolism. The clinical relevance of these HITS remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 18 publications
5
46
0
2
Order By: Relevance
“…However, we found no evidence that any antithrombotic treatment was associated with the occurrence of HITS. This concurs with two previous reports addressing the frequency of HITS in patients with CSE [22, 23]. …”
Section: Discussionsupporting
confidence: 93%
“…However, we found no evidence that any antithrombotic treatment was associated with the occurrence of HITS. This concurs with two previous reports addressing the frequency of HITS in patients with CSE [22, 23]. …”
Section: Discussionsupporting
confidence: 93%
“…Another difference in the selected patient population concerns potential cardiac sources of MES alike atrial fibrillation and in patients with heart valve prostheses. 10 In our study, we excluded patients with possible causes of MES other than the carotid arteries. Furthermore, the majority of our patients (88%) used lipid-lowering therapy, which is known to decrease the presence of MES.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of both MCA insonation and extended time of MES recording increased the sensitivity of the method from 31% to 83.3% (9).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies often included small patient populations, limited data, short recording times, and one insonated MCA (8,9). One trial demonstrated that the sensitivity and specificity of microembolic signal (MES) recordings detection method in patients with potential cardiac sources of embolism (one artery insonation during 30 minutes recording) was 31% and 95% respectively (9).…”
Section: Introductionmentioning
confidence: 99%